Associations of HLA-DP variants with hepatitis B virus infection in southern and northern Han Chinese populations: a multicenter case-control study. - Jin Li (Public Library of Science (PLoS), 2011)
Background Human leukocyte antigen DP (HLA-DP) locus has been reported to be associated with hepatitis B virus (HBV) infection in populations of Japan and Thailand. We aimed to examine whether the association can be replicated in Han Chinese populations. Methodology/principal findings Two HLA-DP variants rs2395309 and rs9277535 (the most strongly associated SNPs from each HLA-DP locus) were genotyped in three independent Han cohorts consisting of 2 805 cases and 1 796 controls. By using logistic regression analysis, these two SNPs in the HLA-DPA1 and HLA-DPB1 genes were significantly associated with HBV infection in Han Chinese populations (P = 0.021∼3.36×10(-8) at rs2395309; P = 8.37×10(-3)∼2.68×10(-10) at rs9277535). In addition, the genotype distributions of both sites (rs2395309 and rs9277535) were clearly different between southern and northern Chinese population (P = 8.95×10(-5) at rs2395309; P = 1.64×10(-9) at rs9277535). By using asymptomatic HBV carrier as control group, our study showed that there were no associations of two HLA-DP variants with HBV progression (P = 0.305∼0.822 and 0.163∼0.881 in southern Chinese population, respectively; P = 0.097∼0.697 and 0.198∼0.615 in northern Chinese population, respectively). Conclusions Our results confirmed that two SNPs (rs2395309 and rs9277535) in the HLA-DP loci were strongly associated with HBV infection in southern and northern Han Chinese populations, but not with HBV progression.